Portable Real Time ECG Monitoring - Mohammed, Tareq Burhan Mahmood; Ail, Mohammed Adnan Younis; Jihad, Mohammed Qasem Ismail; Kazem, Ahmed Ihsan Hassan; Mohammed, Mustafa Shaker Shkur (American Journal of Botany and Bioengineering, 2024)
The use of computers in biomedicine has made a revolution in this field since it greatly facilitated diagnostic procedures, as well as the analysis of the obtained results. Electrocardiography is certainly one of the pioneers of this field. Starting with bulky and heavy devices for registering heart activity, today it has come to the point that for some basic identification of the heart rhythm, it is enough to have a small and cheap sensor plate. Of course, the question of the accuracy of such sensors remains, but they can be used for research, education, and even initial diagnostics. One of such sensors is also presented in this paper. How the sensor is integrated into a system that can successfully register the human heart is also described. Authors of and used ECG sensor as wireless wearable device to be used in portable form. In, the authors showed the potential of medical-grade ECG sensor in medicine, sports, veterinary, etc.